Balance training attenuates postural instability and minimizes falling probability in post stroke patients - HESHAM GALAL MAHRAN,; ABDULLAH G. ALKUSHI, (International Journal of Pharma and Bio Sciences, 2017)
Study objective was to evaluate efficacy of balance training with visual feedback on postural stability and falling in patients with stroke. Forty patients with were selected for this study and their age ranged from forty to sixty years. Patients were randomly assigned into two groups (study and control groups).Patients in both groups participated in the traditional rehabilitation program for stroke, one hour per day/ 5 days/week and for 12 weeks. Balance training using the Biodex Balance System was adding to traditional program for study group as received a twenty minutes balance training daily /5 days/ week and for 12 weeks. Pre and 3 months post- treatment evaluations for stability were conducted using the Biodex Balance System. Twelve weeks after completing the treatment programs there was significant improvements in measurements of balance training in study group. stroke Patients received balance training with visual feedback had significant improvements in comparison with control group in form of attenuating of postural instability and preventing of falling and summarized that balance training was favorable and effective for patients with stroke.